The writing retreat : a novel - Bartz, Julia (New York : Emily Bestler Books, Atria, 2023)
While attending a month-long writing retreat at the estate of a feminist horror writer who issues a life-changing challenge, Alex, determined to win this seemingly impossible contest, ignores the strange happenings around her until the disappearance of a fellow writer leads her on a desperate search for the truth.
Keywords: Women authors -- Fiction; Authors -- Fiction; Contests -- Fiction; Female friendship -- Fiction; Friendship -- Fiction; Missing persons -- Fiction; Writers' retreats -- Fiction; Adirondack Mountains (N.Y.) -- Fiction; Thrillers (Fiction); Psychological fiction